Giant-Cell Tumor of Bone with Pulmonary Metastases:Treatment by Combination of Chemotherapy and Whole-Lung Radiotherapy. Case Report - Özkan, Cenk; Kalacı, Aydıner; Özbarlas, Serdar (Fırat University, 2007)
Giant cell tumors can exhibit malignant behaviour and metastasize in 1% to 9% of patients. Patients with lung metastases from giant cell tumors are treated by surgical resection with very good survival rates. Chemotherapy and radiotherapy have been reserved primarily for patients with unresectable and symptomatic lung metastases. From the authors' literature search, no patients were treated with whole-lung radiotherapy and combined chemotherapy without surgical resection. In this report, we present 8.5 years follow up of a patient with giant cell tumor of bone with pulmonary metastases treated by combination of chemotherapy with whole-lung radiotherapy without surgical resection for lung metastases. ©2007, Fırat University, Medical Faculty

Dev hücreli tümör %1'den %9'a değişen oranlarda malign davranış ve metastaz sergileyebilir. Dev hücreli tümör akciğer metastazlı hastalar cerrahi reseksiyonla çok yüksek oranda tedavi edilir. Kemoterapi ve ışın tedavisi öncelikle semptomatik akciğer metastazlı ve cerrahi olarak rezeke edilemeyen hastalara saklanmalıdır. Cerrahi rezeksiyon yapılmaksızın tüm akciğer ışın tedavisiyle birlikte kemoterapiyle tedavi edilen hastaya literatürde rastlamadık. Bu olgu sunumunda, akciğer metastazı için cerrahi eksizyon yapılmaksızın kemoterapiyle birlikte tüm akciğere ışın tedavisi uygulanan dev hücreli tümör akciğer metastazlı hastanın 8.5 yıllık takibini sunduk. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Akciğer Metastazlı, Kemiğin Dev Hücreli Tümörü: Kemoterapi ve Tüm Akciğer Radyoterapi Tedavi Kombinasyonu. Olgu Sunumu